2020
DOI: 10.1002/1878-0261.12743
|View full text |Cite
|
Sign up to set email alerts
|

An unbiased high‐throughput drug screen reveals a potential therapeutic vulnerability in the most lethal molecular subtype of pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is predicted to become the second leading cause of cancer‐related deaths in the United States by 2020, due in part to innate resistance to widely used chemotherapeutic agents and limited knowledge about key molecular factors that drive tumor aggression. We previously reported a novel negative prognostic biomarker, keratin 17 (K17), whose overexpression in cancer results in shortened patient survival. In this study, we aimed to determine the predictive value of K17 and ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…In a nutshell, the excellent selective therapeutic effect of PTOX and its derivatives on a variety of tumors has attracted increasing attention. Besides the above mentioned tumors, researchers have further developed more PTOX derivatives against other different cancers as well, including pancreatic cancer ( Pan et al, 2020 ), leukemia ( Zhang et al, 2016b ), head and neck squamous cell carcinoma (HNSCC) ( Resendez et al, 2019 ), cervical carcinoma ( Wang et al, 2013 ), etc.…”
Section: Ptox Derivatives As An Anticancer Drug For Various Cancersmentioning
confidence: 99%
“…In a nutshell, the excellent selective therapeutic effect of PTOX and its derivatives on a variety of tumors has attracted increasing attention. Besides the above mentioned tumors, researchers have further developed more PTOX derivatives against other different cancers as well, including pancreatic cancer ( Pan et al, 2020 ), leukemia ( Zhang et al, 2016b ), head and neck squamous cell carcinoma (HNSCC) ( Resendez et al, 2019 ), cervical carcinoma ( Wang et al, 2013 ), etc.…”
Section: Ptox Derivatives As An Anticancer Drug For Various Cancersmentioning
confidence: 99%
“…Our laboratory is currently attempting to determine how testing the K17 status could serve as a predictive biomarker for currently available therapeutic agents for the most aggressive forms of PDAC. In a recent study, 19 we demonstrated that K17 expression correlates with the resistance of PDAC to gemcitabine, and using both in vitro and in vivo models with human and murine PDAC cells and orthotopic xenografts, we found that K17 expression drives increased resistance to gemcitabine and 5-fluorouracil, agents that are currently included in first-line chemotherapy for PDAC. Thus, determining the K17 status at the time of diagnosis could one day help to optimize therapeutic efficacy and to minimize the side effects attributable to agents that are unlikely to provide a survival advantage.…”
Section: Cancer Cytopathology November 2021mentioning
confidence: 82%
“…Thus, the assessment of surrogate markers by immunohistochemistry such as KRT81 and HNF1A [91], CFTR [92], and/or CDH17 and LGALS4 [110], have been proposed for the identification of exocrine-like (HNF1A+, CFTR+, CDH17+ and/or LGALS4+ tumors), squamous (KRT81+), and classical (negative for all above markers) [91,105] PDAC (Figure 3). In addition to KRT81, staining for KRT17 also contributes to delineate tumors falling into the squamous PDAC [111] (Figure 3) and to identify tumors that are chemoresistant to gemcitabine-and 5-FU-based regimens [112]. Hence, simplified PDAC stratification by assessment of expression profiles for a restricted number of proteins provides the opportunity to define clinically relevant molecular subtypes of PDAC in routine diagnostic laboratories, in both resectable [92,105,113] and advancedstage tumors [105] undergoing, e.g., volumetric whole-tumor analysis via radiomic-based investigations [113].…”
Section: Molecular Biomarkers For Risk Stratification Of Pdac Patientsmentioning
confidence: 99%